Cutaneous Squamous Cell Carcinoma with Signet-Ring Cell Component and CDX2 Expression in a Patient Treated with PD-1 Inhibitor: A Case Report of a Common Tumor with Unusual Differentiation - Sherehan Zada; Jeremiah Tao; Maria Del Valle Estopinal (Case Reports in Pathology)
Signet-ring cell squamous cell carcinoma (SRCSCC) is an uncommon variant of cutaneous SCC that has been reported in the head and neck region. Herein, we present a case of a 56-year-old female with a cutaneous SCC that recurred after surgical excision, during treatment with cemiplimab (a programmed death receptor-1 (PD-1) inhibitor). Histologically, the recurrent SCC revealed a second component characterized by the presence of signet-ring-like cells (SRLCs). Immunohistochemical studies demonstrated that the tumor cells were positive for P63, CK5/6, CDX2, and P53 while negative for P16, CK7, CK20, and CD68 stains. An abnormal expression of B-catenin was also observed in the tumor. To our knowledge, SRCSCC developing during treatment with an immune checkpoint inhibitor has not been documented in the literature. Our findings suggest a form of acquired SCC cell resistance to immunotherapy that might involve CDX2-related pathways.